2022
DOI: 10.1016/j.atherosclerosis.2021.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Pre-infection HDL-cholesterol levels and mortality among elderly patients infected with SARS-CoV-2

Abstract: Background and aims Low HDL-cholesterol (HDLc) concentration is associated with a greater risk of infection-related mortality. We wanted to evaluate the relationship between pre-infection HDLc levels and mortality among older patients infected with SARS-Cov-2. Methods This is a population-based, cohort study, comprising all individuals residing in Madrid (Spain) born before 1 January 1945, and alive on 31 December 2019. Demographic, clinical, and analytical data were ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 31 publications
1
7
0
2
Order By: Relevance
“…Recombinant HDL-C therapy has become a new treatment for severe sepsis [ 14 ]. Patients with severe COVID-19 and mortality have been displayed to have lower HDL-C concentrations [ 15 ]. As society enters a post-COVID-19 era, the determinants of short- and long-term mortality from the first wave of COVID-19 are of interest.…”
Section: Introductionmentioning
confidence: 99%
“…Recombinant HDL-C therapy has become a new treatment for severe sepsis [ 14 ]. Patients with severe COVID-19 and mortality have been displayed to have lower HDL-C concentrations [ 15 ]. As society enters a post-COVID-19 era, the determinants of short- and long-term mortality from the first wave of COVID-19 are of interest.…”
Section: Introductionmentioning
confidence: 99%
“…Whether cause or a consequence of COVID-19 disease or how lipid metabolism is affected by the infection is not a question that could be answered by this cross-sectional study. Potential mechanisms related to COVID-19 dyslipidemia and few previous recently published studies also showed this association between low levels of HDL-c and the severity of COVID-19 pneumonia besides a protective factor against SARS-2 infection [ [6] , [9] , [33] , [34] , [35] , [36] , [37] ]. Previously to the SARS-Cov-2 pandemia it was pointed by several studies changes in the quantity and composition of HDL in infections and community acquired pneumonia.…”
Section: Discussionmentioning
confidence: 90%
“…In the study by Mostaza et al, 41 which examined the prognostic effect of lipid levels before COVID-19 infection, an inverse association was found between a high HDL-C level and mortality in older individuals before the disease. 41 This is a similar status to our study. In another study by Masana et al, 42 serum lipid levels of 1305 patients were examined.…”
Section: Discussionmentioning
confidence: 96%